Urgensi Perubahan Paradigma Hukum dalam Pengelolaan Sumber Daya Air Nasional - Jundiani, Jundiani (ULUL ALBAB Jurnal Studi Islam, 2004)
This paper discusses operational and legal paradigm aspects of water resources management inÂ· Indonesia. Principles and concepts of anthropocentrims and holism are presented. Issues discussed are legal idiology and legal paradigm of national water resources management. The paper concludes with an outlook on the needs for development of legal paradigm and community-based water resources management.